2015
DOI: 10.1111/sode.12111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bidirectionality of Emotion Understanding and Classroom Behavior with Spanish‐ and English‐speaking Preschoolers Attending Head Start

Abstract: The present study investigated time-dependent relationships between emotion understanding and the behavioral adjustment of preschoolers over a single school year using a latent variable structural equation modeling framework. Teacher reports of child behavior (hyperactivity, emotion symptoms, conduct problems, peer problems, and prosocial behavior) and performance assessments of emotion understanding were obtained twice at a 6-month interval for a sample of 281 preschoolers (159 boys and 122 girls, with mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Consistent with this perspective, researchers have found that relations between teacher‐reported social competence and children’s academic achievement were mediated by gains in emotion knowledge (Torres, Domitrovich, & Bierman, ). Other researchers have investigated bidirectional relations between aspects of preschoolers’ behavior and emotion knowledge and found relations from children’s behavior to emotion knowledge, but not the other way around (Strand, Barbosa‐Leiker, Arellano Piedra, & Downs, ). Researchers should examine associations between social knowledge and social competencies longitudinally so as to be able to control for earlier levels of social abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this perspective, researchers have found that relations between teacher‐reported social competence and children’s academic achievement were mediated by gains in emotion knowledge (Torres, Domitrovich, & Bierman, ). Other researchers have investigated bidirectional relations between aspects of preschoolers’ behavior and emotion knowledge and found relations from children’s behavior to emotion knowledge, but not the other way around (Strand, Barbosa‐Leiker, Arellano Piedra, & Downs, ). Researchers should examine associations between social knowledge and social competencies longitudinally so as to be able to control for earlier levels of social abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For boys, emotion understanding mediated the relationship between emotion socialization and children’s internalizing behaviors. A more recent cross‐cultural study of emotion understanding in 281 preschoolers (159 boys; M age = 4 years) from English ( N = 158) and Spanish‐speaking ( N = 123) backgrounds investigated the relationship between child emotion understanding and externalizing child behavior problems at different time points over 6 months (Strand, Barbosa‐Leiker, Piedra & Downs, 2015). They found evidence of a stronger and more complex bi‐directional relationship between child emotion understanding and behavior problems for Spanish‐speaking girls compared to boys and for all English‐speaking children.…”
Section: Parental Emotion‐related Socialization Behaviors (Ersbs)mentioning
confidence: 99%
“…Both recognition and knowledge are critical to children's understanding of the actual emotional experiences of the self and others within specific situations (both emotion‐eliciting and nonemotion eliciting) and likely affects how children understand and represent significant personal experiences (Frijda, ; Wang, ). Numerous studies show that children's emotion understanding is an important predictor of children's social functioning and classroom adjustment (Denham et al, ; Garner & Waajid, ; Miller et al, ; Schultz, Izard, Ackerman, & Youngstrom, ; Strand, Barbosa‐Leiker, Arellano Piedra, & Downs, ). The majority of these studies, however, focus on the emotion recognition component of emotion understanding, and specifically in early childhood.…”
Section: Parents' Emotion‐related Beliefsmentioning
confidence: 99%